Fracture fixation of the Odontoid process of the axis through an osseous-axis pin in Cuba. A case report. - José Ramón Tejera del Valle (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
The fractures of the odontoid process of the Axis has been a polemic topic for many years. The alternative technique of placing a fixation screw directly across the fracture site, reattaching the odontoid to the body of C2 had been gained defensors in the actuality in the world. The topic was reviewed, and the seventh case knowned was been operated in Cuba by this technique was presented. This intervention was realized in the Department of Neurosurgery of Cienfuegos. Current considerations are emitted.